Mom's Education Determine By Receiving Basic Immunization In Babies - Yuanita Ani Susilowati; Heni Lestari; Elizabeth Ari Setyarini; Ferdinan Sihombing (Jambura Nursing Journal, 2023)
Immunization is an effort to generate active immunity against a disease. The basic immunization coveraged in Mukapayung Village in 2021 is 67.4%, while the basic immunization achievement target set by the government is 98%. The purpose of this study was to determine the relationship between mother's knowledge and education with basic immunization receipts for infants 0-12 months in Mukapayung Village. The research method uses a descriptive correlation design, cross sectional approach with a total sample. Respondents amounted to 110 mothers who had babies aged 0-12 months. Data collection using a 20-item knowledge questionnaire. Validity and reliability test were carried out in Karang Tanjung Village on 30 respondents and the results were obtained validity from 0.411 to 0.566 with a reliability value of 0.917 which means very reliable. The results showed that there was no relationship between mother's level of knowledge and basic immunization reception for infants 0-12 months with p value 0.501> α but there was a significant relationship between mother's education level and basic immunization reception for infants 0-12 months with p value 0.011 < α. Discussion, the level of knowledge and education is not always in line with the behavior or actions related to basic immunization for infants 0-12 months, because many factors affect a person's knowledge. Conclusion, the higher the education of the mother, the more she understands the importance of maintaining children's health through prevention of various diseases by providing basic immunization. since early stage.